Sosialisasi penanggulangan kenakalan remaja di desa simartolu kecamatan sosopan kabupaten padang lawas - Hasibuan, Sutan Botung Hasibuan; Harahap, Yusniar; Syafaruddin; Nasution, Ismail; Nasution, Nur Hakima Akhirani (Institute of Computer Science (IOCS), 2024)
Adolescence is the transition period from childhood to adulthood. A teenager can no longer be considered a child, but he is not mature enough to be considered an adult. In adolescence he is looking for a lifestyle that best suits him, and he will often take action through trial and error. From this trial and error method, parents have an important role to supervise and protect adolescents so that they do not fall into juvenile delinquency such as promiscuity, drugs, alcohol, speeding, fighting, stealing, skipping school and bullying. One solution to overcome and prevent juvenile delinquency is to hold a socialisation of juvenile delinquency and solutions to handle it to the surrounding community. In addition, in overcoming juvenile delinquency can also be divided into preventive action, repressive action, curative action, and rehabilitation